2007
DOI: 10.1126/science.1144318
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Redox Sensor in PKGIa Enables Oxidant-Induced Activation

Abstract: Changes in the concentration of oxidants in cells can regulate biochemical signaling mechanisms that control cell function. We have found that guanosine 3',5'-monophosphate (cGMP)-dependent protein kinase (PKG) functions directly as a redox sensor. The Ialpha isoform, PKGIalpha, formed an interprotein disulfide linking its two subunits in cells exposed to exogenous hydrogen peroxide. This oxidation directly activated the kinase in vitro, and in rat cells and tissues. The affinity of the kinase for substrates i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

20
387
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 429 publications
(407 citation statements)
references
References 26 publications
20
387
0
Order By: Relevance
“…S6). We speculate that suppression of eNOS activity may lead to enhanced mitochondrial respiration (1)(2)(3)45) and thereby increase H 2 O 2 production, which then promotes CaMKK␤ activation by oxidation of key thiols (5,8) either in CaMKK␤ or in an upstream kinase or phosphatase, leading then to AMPK phosphorylation (13,20) and activation (see model in Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S6). We speculate that suppression of eNOS activity may lead to enhanced mitochondrial respiration (1)(2)(3)45) and thereby increase H 2 O 2 production, which then promotes CaMKK␤ activation by oxidation of key thiols (5,8) either in CaMKK␤ or in an upstream kinase or phosphatase, leading then to AMPK phosphorylation (13,20) and activation (see model in Fig. 8).…”
Section: Discussionmentioning
confidence: 99%
“…The signaling pathways leading to activation of CaMKK␤ are incompletely understood, although a role for calcium-calmodulin has been established. A growing literature on protein kinase regulation has identified redox-active cysteine thiols as critical determinants of the activity of some kinases (4,8). For example, the cGMPdependent protein kinase undergoes oxidation at key thiol residues, leading to kinase activation independent of cGMP (4, 8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an emerging concept identifies two types of disulfide bonds, a structural group and a redox-sensitive regulatory group, with the latter having direct functional consequences for the cell [27,28]. After bacterial transcription factor OxyR was found to be directly activated by thiol oxidation [29], increasing numbers of reports have recently shown that covalent modification of cysteines by disulfide formation can activate proteins in mammalian cells [30][31][32] and that disulfides are rapidly formed on cell surfaces in response to changes in the cellular redox state [28]. In agreement with these novel concepts, our finding that oxidative modification of caspase-9 can promote its activation has provided a previously undescribed perspective of how oxidative stress induces apoptosis; in addition to the Figure 5 Cys403 mutation blunted the sensitivity of caspase-9 to H 2 O 2 -induced auto-cleavage and decreased the formation of disulfide-dependent complex and apoptosomes.…”
Section: Discussionmentioning
confidence: 99%
“…This microvascular hypo-responsiveness to nitrates is reversed when nitroglycerine is administered with L-cysteine or N-acetylcysteine [12], presumably by generating S-nitrocysteine. More recently, studies by Eaton and coworkers [13,14] have established that the molecular 'targets' for organic nitrates are sensitive to changes in oxidative stress. In particular, protein kinase G becomes less sensitive to nitric oxide under increased redox stress, while responding more readily to other activators such as Snitrocysteine and hydrogen peroxide.…”
Section: Advances In Nitrate Pharmacology From Coronary Microvascularmentioning
confidence: 99%